Organizational Psychology in Arequipa: Past, present and troubles - Arias Gallegos, Walter L. (2024)
In this paper, we analyze the development of organizational psychology in Arequipa City (Peru), from the first teaching issues and applications to the academic productivity and its research trends, which have been strengthened in the lats years. First, we briefly review the history of organizational psychology in the world including Peru, so then we are going to focus in the registered advances in Arequipa City, considering the research articles published in different journals of psychology. We finish with a review of the challenges that organizational psychology must face in Arequipa City, in order to gain its academic consolidation, as subdiscipline of the psychological science.